Retail Banks’ Challenges and Opportunities from Vision and Strategy to Managing People, Processes and Capital - Omarini, Anna (Current Aspects in Business, Economics and Finance Vol. 3, 2022)
Bankers have usually viewed a wide range of external factors, including deregulation and reregulation, competition, financial innovation, and technology, as significant external drivers for changing their visions, strategies, and business models. The aim of the chapter is to outline the retail bank’s evolution from the past to the ongoing scenario where FinTech companies and new competitors are transforming the industry and boosting banks to react consistently. After a brief overview of the present challenges, the chapter is focused on how banks are undertaking their transformation in the market to regain their customers’ everyday lives centrality.